Dampak Program Pencegahan Penularan Infeksi HIV dari Ibu ke Anak (PPIA) - Erliyani; Rahmadani, Mutia; Rahayu, Nisfia; Fatimah, Nur; Sulistyani, Tyas; Windayanti, Hapsari (Universitas Ngudi Waluyo, 2023)
HIV/AIDS is a type of virus that can cause a decrease in human immunity. Pregnant women with HIV/AIDS have the possibility of giving birth to a child with HIV. HIV/AIDS is a global problem, increasing every year. The Prevention of Mother-to-Child Transmission of HIV (PPIA) program has been proven to be a very effective intervention for preventing mother-to-child transmission of HIV. Low coverage of interventions to prevent mother-to-child transmission of HIV (PPIA), compliance, and care retention rates among HIV-positive pregnant women are factors that contribute to the high rate of mother-to-child transmiss ion of HIV. The method used in preparing this research is Literature Review. The data collection used in this research uses data from the Google Scholar and PUBMED databases. To carry out this literature review, it includes inclusion of: journals published in 2017–2020 and can be accessed in full text PDF in Indonesian and English. while the exclusion criteria for this research were secondary articles or journals. Researchers found 10 journals which would then be analyzed for titles, research methods, results and discussions and determined for their suitability. The screening process in accordance with inclusion and exclusion resulted in 6 journals being reviewed and in accordance with the research objectives. The results of the literature review of these 6 articles show that there is an impact of the Program for Preventing HIV Transmission from Mother to Child (PPIA). The PPIA program not only focuses on the welfare of pregnant women, but also on protecting newborns from HIV infection. This review shows that effective approaches and techniques are being implemented to reduce the risk of HIV transmission to mothers and babies. PPIA improves maternal and child health by preventing the spread of HIV infection in countries around the world. There is evidence of the positive impact of PPIA on primary health services for mothers and children. Based on the results of the literature review of these 6 articles, intervention for pregnant women infected with HIV can be carried out with a program to prevent transmission of HIV infection from mother to child (PPIA). The program to prevent the transmission of HIV infection from mother to child (PPIA) has proven to have a very effective impact in reducing HIV transmission to babies . Abstrak HIV/AIDS merupakan sejenis virus yang dapat menyebabkan turunnya kekebalan tubuh manusia. Pada wanita hamil dengan HIV/AIDS mempunyai kemungkinan melahirkan anak dengan HIV. HIV/AIDS ini menjadi permasalahan global, meningkat setiap tahunnya. Program Pencegahan Penularan HIV dari Ibu ke Anak (PPIA) telah terbukti sebagai intervensi yang sangat efektif untuk mencegah penularan HIV dari ibu ke anak. Rencahnya cakupan intervensi pencegahan penularan HIV dari ibu keanak (PPIA), kepatuhan, dan tingkat retensi perawatan pada ibu hamil dengan HIV positif merupakan faktor yang berkontribusi terhadap tingginya angka penularan HIV dari ibu ke anak. Metode yang digunakan dalam penyusunan penelitian ini yaitu Literature Review. Pengumpulan data yang digunakan dalam penelitian ini adalah menggunakan data pada database google scholar dan PUBMED. Untuk melakukan tinjauan literature ini meliputi inklusi : jurnal terbitan tahun 2017– 2020 dan dapat diakses secara full text pdf berbahasa Indonesia dan Bahasa Inggris. sedangkan kriteria eksklusi pada penelitian ini artikel atau jurnal sekunder. Peneliti menemukan sebanyak 10 jurnal yang kemudian akan dianalisa judul, metode penelitian serta hasil dan pembahasan serta ditentukan kelayakannya. Proses screening sesuai dengan inklusi dan eksklusi menghasilkan 6 jurnal yang ditelaah dan sesuai dengan tujuan penelitian. Hasil literature review dari 6 artikel tersebut, menunjukkan bahwa ada Dampak dari Program Pencegahan Penularan HIV dari Ibu ke Anak (PPIA). Program PPIA tidak hanya berfokus pada kesejahteraan ibu hamil, namun juga pada perlindungan bayi baru lahir dari infeksi HIV. Tinjauan ini menunjukkan bahwa pendekatan dan teknik yang efektif diterapkan untuk mengurangi risiko penularan HIV pada ibu dan bayi. PPIA meningkatkan kesehatan ibu dan anak melalui pencegahan penyebaran infeksi HIV di negara-negara seluruh dunia. Terdapat bukti dampak positif PPIA pada layanan kesehatan primer bagi ibu dan anak. Berdasarkan hasil literature review dari 6 artikel tersebut, intervensi bagi ibu hamil yang terinfeksi HIV dapat dilakukan dengan program pencegahan penularan infeksi HIV dari ibu ke anak (PPIA). Program pencegahan penularan infeksi HIV dari ibu ke anak (PPIA) terbukti berdampak sangat efektif dalam mengurangi penularan HIV pada bayi.